Improvement in effectiveness of diamond in strengthening the porous aluminium composite - Parveez, Bisma; Jamal, Nur Ayuni; Maleque, Md. Abdul; Ahmad Azhar, Ahmad Zahirani; Mohd Zaki, Hafizah Hanim; Aabid, Abdul; Baig, Muneer (ScienceDirect, 2023)
In this study, an aluminum (Al) alloy matrix reinforced with uncoated and titanium (Ti) -coated diamond were developed using powder metallurgy technique where polymethylmethacrylate (PMMA) particles were employed as space holders. The weight % of uncoated and coated diamond varied as (0, 6, 9, 12, 15, and 20 wt.%). Microstructural and elemental analysis was examined using scanning electron microscopy and energy dispersive spectroscope, respectively. The relative density and porosity that were in the range of 0.72–0.92 and 31–44% respectively, were measured using Archimedes principle. The compressive properties were measured and correlated with microstructure observations. The microstructure of the composite samples revealed presence of well-defined macro pores with good interfacial integrity. The X-ray diffraction revealed the presence of strengthening phases such as Al2Ti, Mg2Sn, AlB12, Cu5Sn6, Al12Mg17 and MgB2 phases formed as a result of addition of metal additives in Al matrix. Further improvement in the strength was obtained by using Ti-coated diamond particles as reinforcement. As Ti formed a good interface between the Al alloy matrix and the diamond thereby preventing the formation of undesirable carbide phases. There was an improvement in plateau stress and energy absorption capacity of 82 and 88% as compared to unreinforced porous sample. The maximum values obtained for the plateau stress and energy absorption capacity were 45.12 MPa and 13.68 MJ/m3 respectively for 9 wt.% of Ti-coated diamond reinforced composites. Uncoated diamond reinforced composites, on the other hand, reduced the strength of porous Al alloy matrix due to the formation of brittle intermetallic compound such as carbides (Al2C3) at the interface. As a result, the coated diamond particle surface modifies and improves the wettability of the Al alloy matrix and diamond interface.